Hemoglobin Stimulates the Expression of Adamts-5 and -9 by Synovial Cells; A Possible Cause of Cartilage Damage after Intra-articular Bleeding. Issue 7 (21st July 2017) - Tajima, Takuya; Chosa, Etsuo; Taniguchi, Noboru; YAMAGUCHI, Nami
Objectives: A disintegrin and metalloprotease with thrombospondin motifs (ADAMTS)-5 and -9 play an important pathologic role in matrix degeneration. Aggrecanase-mediated aggrecan degradation is a significant and critical event in early-stage osteoarthritis. To determine the effect of hemoglobin (Hb) on the ability of synovial tissues to produce ADAMTS family that play important roles in the degradation of articular cartilage, examining the influence of Hb by synovial cells in vitro experimental system. Methods: Synovial tissues were obtained from five young patients with meniscus injury. The mean age of patients was 14 years (range: 10-16). The experimental design was reviewed and approved (Accession No. 405) by the Committee for Ethics at the Faculty of Medicine, Miyazaki University. The procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1975, as revised in 2000. We obtained written, informed consent from all patients before entering the study. Primary cultures of human knee synovial cells were treated with different doses of human Hb (0, 25, 50, 100 μg/ml) for the preliminary examination. The culture media were collected 24 h after Hb-treatment. In the time-course studies, cells were treated with 100 μg/ml Hb and culture media were taken at 6, 12, and 24 h. To identify the proteins those are responsible for aggrecanase activity, Western blot analysis using antibodies against human ADAMTS-5, -8, -9, and -10, Enzyme-Linked ImmunoSorbent Assay (ELISA) and gene expression for ADAMTS-5, and -9 were examined. Results: Western blot analysis revealed that Hb-treatment resulted in the detection of ADAMTS-5 and -9 proteins in a dose-, and time-dependent manner. Neither control nor Hb-treated medium showed immunoreactivity against anti-ADAMTS-8, and -10 IgG. In a dose-dependency study which were measured by ELISA, the peak immunoreactivity was confirmed at Hb concentration of 100μg/ml. Even if 25μg/ml treated with Hb at 24h, there are significantly increasing expression compared with the control group both in the results of ADAMTS-5, and -9 (p<0.05). In a time-course study analyzed, the levels of ADAMTS-5 and -9 antigen level in the conditioned medium which were measured by ELISA reveals significantly increasing expression at 6, 12, and 24h in the Hb-treated group compared with the results of control group (p<0.05). Hb evoked significantly expression of ADAMTS-9 mRNA at 12 and 24 hours (p<0.05). Hb induced highly expression of ADAMTS-9 at 6 hours without significant difference. The mRNA level of ADAMTS-5 was not enhanced by Hb, significantly. Conclusion: Our results suggest a possible role of Hb for joint damage after intra-articular bleeding. Hb induces the expression of ADAMTS family proteinase such as ADAMTS-5 and -9 by synovial cells at low doses even at an acute phase. These findings suggest that single instance of intra-articular bleeding during trauma or sports injury could affect on articular cartilage metabolism deleteriously during an acute phase. Immediate treatment for intra-articular bleeding, such as washing out and removing the blood from the joint cavity, may be required regardless of whether it occurs once or repeatedly.